Export behavior of the Brazilian coffee agribusiness and interactions with production elements (Research, Society and Development, 2021)
Coffee has relative importance for the trade balance and for the productive structure of Brazilian agribusiness, although it presents difficulties in adding value to exports. In order to analyze the behavior of Brazilian coffee industrial-agricultural exports and its relationship with production agents, this study considered data from the years 2001 to 2019, which are related to production, area and production feet. Data on the quantity and value of exported coffee were also evaluated. All variables were subjected to statistical correlation analysis. Production quantity, productivity (bags per hectare), area and planted trees were inversely related to exchange rate variations, with positive responses of the quantity of productive trees to price increases. Coffee exports were more concentrated in the first stage of the industrial-agricultural chain, with a small increase in soluble coffee and successive decreases in roasted and ground coffee, which accounts for 0.1% of all coffee exports in the country. Even though the industrial-agricultural has shown average increases of 4% and 3% annual in the volume of exported beans and soluble coffee, the production chain is experiencing stagnation in the values sold in the foreign market, which correlate negative way with the exchange rate. These results show that the strong concentration in the initial stage of the Brazilian coffee production chain is sensitive to exchange rate variations, while soluble, roasted and ground coffees have difficulties in expanding in the international market, culminating in the challenge of creating valuation policies for these products.